Magnetic Materials: Structure and Magnetic Property Control of Copper Hydroxide Acetate by Non‐Classical Crystallization (Small 9/2017). Issue 9 (March 2017) - Song, RuiQi; Krasia‐Christoforou, Theodora; Debus, Christian; Cölfen, Helmut
Abstract : A method for synthesizing inorganicorganic composite materials with tunable magnetic properties is developed by using copperincorporated block copolymer micelles as precursors in combination with ultracentrifugation induced crystallization. In article number 1602702, H. Cölfen and co‐workers show that magnetic properties of these materials can be controlled by varying polymer microstructures that change the structures of copper hydroxide acetate.